Effects of Social Media Usage on Consumers’ Purchase Intention in Social Commerce: A Cross-Cultural Empirical Analysis - Hu, Shangui; Zhu, Zhen (Frontiers in Psychology, 2022)
Social commerce has produced enormous economic benefits as well as challenges for organizations, individuals, and industries. However, social media usage does not necessarily generate users’ intention to purchase on social commerce websites. How social media usage influences users’ purchase intention on social commerce websites still deserves more scholarly attention and this seems particularly important when social commerce transcends borders and countries. Taking an interdisciplinary perspective, the current study adopted a survey research method and identified the roles of social media usage in arousing users’ purchase intention on social commerce websites in a culturally diversified environment. The data was collected from 2,058 international students coming from 135 countries and was analyzed using MPLUS based structural equation modeling. The research unveils the pathway whereby social media usage serves to generate users’ purchase intention on social commerce websites. Importantly, users’ cultural intelligence has been found to play a significant role mediating the effects of social media usage on users’ intention. Further, cultural distance was found to attenuate the effects of social media usage on cultural intelligence. Based on the research findings, the study suggests that social commerce practitioners should be fully aware of the enabling roles of social media and cultural intelligence as well as the deterring role of cultural distance when arousing customers’ purchasing intention in cross-cultural business operations. Any measures facilitated by social media usage to improve international consumers’ cultural intelligence and mitigate the negative effects of cultural distance are supposed to be effective to enhance their purchasing intention. Accordingly, the study confirms the mutually melt and integrative relationships between information technology advancement and business prosperity in cross-cultural environment, which eventually contribute to sustainable development of society.